RESEARCH OF NON-BINARY SUBDIVISION OF TWO-DIMENSIONAL SEQUENCES BASED ON LINEAR COMBINATIONS OF B-SPLINES - Приставка, П. О.; Нічіков, Є. П. (Science-based technologies, 2014)
A general statement of the problem of conducting non-binary subdivision of two-dimensional sequences based on linear combinations of the B-splines that are related to the interpolar on average, is proposed. General method for determining the location of the samples for projection of numerical sequences described. The partial cases of spline operators are shown in the form of a discrete convolution of the sequence of samples and the corresponding masks. Digital raster image have been enlarged three times by width and height. Methods were used continuous approximation using spline S2,1 and partial cases of this spline. Experiments show the performance increase when scaling images to the predefined ratio. Further research can be aimed at the generalization of the presented procedures of non-binary subdivision to the case of multidimensional sequences.